2023
DOI: 10.1111/hepr.13947
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated metabolic factors of nonalcoholic fatty liver disease in the general population from 2014 to 2018 in Japan: A large‐scale multicenter retrospective study

Hideki Fujii,
Yuichiro Suzuki,
Koji Sawada
et al.

Abstract: AimThe prevalence of nonalcoholic fatty liver disease (NAFLD) is increasing worldwide. The aim of this study was to determine the recent prevalence and clinical characteristics of NAFLD in Japan.MethodsThis study initially included 410,061 retrospectively enrolled adults from the medical health checkup registry for metabolic syndrome, chronic kidney disease, and fatty liver in Japan (MIRACLE‐J; UMIN‐CTR no. UMIN000049419), who were evaluated between 2014 and 2018 at 13 health centers in Japan. Subjects consumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…In the Japanese general population, the prevalence of NAFLD was reported to decrease after peaking in the 50s for men and in the 60s for women. 46 In addition, advanced liver fibrosis in non-alcoholic steatohepatitis is often accompanied by a reduction in hepatic fat contents, known as burnt-out non-alcoholic steatohepatitis. 47 Based on the aforementioned, we hypothesized that age and liver fibrosis were related to the prevalence of MASLD in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…In the Japanese general population, the prevalence of NAFLD was reported to decrease after peaking in the 50s for men and in the 60s for women. 46 In addition, advanced liver fibrosis in non-alcoholic steatohepatitis is often accompanied by a reduction in hepatic fat contents, known as burnt-out non-alcoholic steatohepatitis. 47 Based on the aforementioned, we hypothesized that age and liver fibrosis were related to the prevalence of MASLD in this present study.…”
Section: Discussionmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide and is estimated to affect 25% of the population. [1][2][3] NAFLD increases the prevalence of hepatocellular carcinoma or liver failure and is an economic health burden. [4][5][6][7][8][9][10][11] In August 2023, a consensus group consisting of multiple academic institutions proposed a reclassification of NAFLD, introducing a new nomenclature of steatotic liver disease (SLD) and its corresponding subgroups, because the term NAFLD may be stigmatizing and has concerns regarding potential discriminatory implications.…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence of NAFLD was approximately 37% in 2019 [9]. However, the prevalence varies by country: India reported 38.6% [10], Japan 25.8% [11], China 29.8% [12], Korea 30.3% [13], and Sri Lanka 32.6% [14]. A study conducted in Bangladesh found an overall NAFLD prevalence of 33.86% across genders and urban-rural regions [6].…”
Section: Introductionmentioning
confidence: 99%